Management, valuation, and risk for human capital and human assets : building the foundation for a multi-disciplinary, multi-level theory - Russ, Meir, 1968-; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2014)
Perspectives on Human Capital and Assets goes beyond the current literature by providing a platform for a broad scope of discussion regarding HC&A, and, more importantly, by encouraging a multidisciplinary fusion between diverse disciplines.
Keywords: Human capital -- Management; Knowledge management; Organizational change